Insulin-like growth factor-I concentration and risk of prostate cancer: results from the European Prospective Investigation into Cancer and Nutrition. - Price, A; Allen, N; Appleby, P; Crowe, F; Travis, R; Tipper, S; Overvad, K; Grønbæk, H; Tjønneland, A; Johnsen, N; Rinaldi, S; Kaaks, R; et al. (2012)
BACKGROUND: High circulating insulin-like growth factor-I (IGF-I) concentrations have been associated with increased risk for prostate cancer in several prospective epidemiological studies. In this study, we investigate the association between circulating IGF-I concentration and risk of prostate cancer over the long term in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. METHODS: In a nested case-control design, 1,542 incident prostate cancer cases from eight European countries were individually matched to 1,542 controls by study center, age at recruitment, duration of follow-up, time of day, and duration of fasting at blood collection. Conditional logistic regression models were used to calculate risk for prostate cancer associated with IGF-I concentration, overall and by various subgroups. RESULTS: Circulating IGF-I concentration was associated with a significant increased risk for prostate cancer [OR for highest vs. lowest quartile, 1.69; 95% confidence interval (CI), 1.35-2.13; P(trend) = 0.0002]. This positive association did not differ according to duration of follow-up [ORs for highest vs. lowest quartile were 2.01 (1.35-2.99), 1.37 (0.94-2.00), and 1.80 (1.17-2.77) for cancers diagnosed <4, 4-7, and >7 years after blood collection, respectively (P(heterogeneity) = 0.77)] or by stage, grade, and age at diagnosis or age at blood collection (all subgroups P(heterogeneity) >0.05). CONCLUSION: In this European population, high circulating IGF-I concentration is positively associated with risk for prostate cancer over the short and long term. IMPACT: As IGF-I is the only potentially modifiable risk factor so far identified, research into the effects of reducing circulating IGF-I levels on subsequent prostate cancer risk is warranted.